VALIDITY OF WIDE USE OF POLYMER COMPOSITE MATERIALS - Khusanov Yunusali Yuldashaliyevich; Halikova Dilafuruz Abdumukhtar kizi (Western European Studies, 2024)
This paper examines the widespread application of Polymer Composite Materials (PCMs) across diverse industries, emphasizing their pivotal role in enhancing technological development. With superior properties such as strength, ductility, and corrosion resistance, PCMs significantly contribute to weight reduction in aerospace components, as evidenced by their 35% incorporation in Boeing 737 and Airbus A320 aircraft. The study delves into the challenges encountered during PCM machining, particularly in cutting mechanisms and material defects, highlighting the need for comprehensive research in this domain. Despite these challenges, the economic advantages and technological progress facilitated by PCMs remain undeniable. The paper underscores the critical balance between harnessing the benefits of PCMs and addressing machining complexities to ensure their continued validity in a wide range of applications.
Keywords: Polymer Composite Materials; Aerospace industry; Fiberglass materials